2021
DOI: 10.1111/1744-7917.12948
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific mortality and fecundity of a spider mite under diet restriction and delayed mating

Abstract: Numerous experimental life‐history studies on aging are mainly baised on two classical models—fruit fly Drosophila melanogaster (Meigen) and nematode Caenorhabditis elegans (Maupas)—with relatively little attention given to other organisms with different life‐history characters. Two‐spotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae) differs from many other arthropods in that the females continue their growth in the early adult stage and can reproduce sexually and asexually. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
5
1
Order By: Relevance
“…Contrary to what has been observed in Drosophila melanogaster (Partridge et al, 2005) or spider mites for instance (Li and Zhang, 2021), where dietary restriction lowers the risk of death but affects only marginally the rate of ageing itself, dietary restricted Collembola achieved lifespan extension by maintaining a low basal adult mortality rate and by setting back the onset of actuarial senescence and slowing its rate. This plasticity, especially remarkable in one clade (A), enabled the springtails not only to double or almost triple their life expectancy but also to change the qualitative pattern of senescence: a change in diet can trigger a shift from strong negative actuarial senescence to negligible senescence.…”
Section: Figurecontrasting
confidence: 76%
See 2 more Smart Citations
“…Contrary to what has been observed in Drosophila melanogaster (Partridge et al, 2005) or spider mites for instance (Li and Zhang, 2021), where dietary restriction lowers the risk of death but affects only marginally the rate of ageing itself, dietary restricted Collembola achieved lifespan extension by maintaining a low basal adult mortality rate and by setting back the onset of actuarial senescence and slowing its rate. This plasticity, especially remarkable in one clade (A), enabled the springtails not only to double or almost triple their life expectancy but also to change the qualitative pattern of senescence: a change in diet can trigger a shift from strong negative actuarial senescence to negligible senescence.…”
Section: Figurecontrasting
confidence: 76%
“…Similarly, some studies have revealed a remarkable qualitative intraspecific variation in the age pattern of reproduction and mortality in species like dogs (Kraus et al, 2013), social insects (Münch et al, 2008), reptiles and amphibians (Cayuela et al, 2020a;Tully et al, 2020;Cayuela et al, 2021) or hexapods (Mallard et al, 2015;Li and Zhang, 2021), while other studies have found similar age-specific mortality patterns across populations of the same species (Reichard, 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The number of surviving females and their eggs were assessed four days after infestation. With these two measures, we calculated fecundity per female assuming linear mortality [ 52 ] by using [total eggs]/[(alive females + total females)/2] and using these numbers as the average per female. This equation accounts for differential female mortality, which is measured at the end of the assay and thus enables a more accurate representation of per capita fecundity.…”
Section: Methodsmentioning
confidence: 99%
“…Following four days of infestation (day 4), the number of surviving females on the leaflet and the number of eggs laid were counted. With these two measures, we calculated fecundity per female assuming linear mortality (Li & Zhang, 2022) by using: [total eggs] / [(alive females + total females)/2] and using these numbers as the average per female. There were ten to 11 and eight to nine replicates for each population, on WT and def-1, respectively.…”
Section: Fecundity Of T Urticae From Field-collected Populations On W...mentioning
confidence: 99%